Answer:
( [tex]\frac{1}{2}[/tex], 0 )
Step-by-step explanation:
Given the 2 equations
4x + 3y = 2 → (1)
2x - 3y = 1 → (2)
Adding (1) and (2) term by term will eliminate the y- term, that is
6x = 3 ( divide both sides by 6 )
x = [tex]\frac{3}{6}[/tex] = [tex]\frac{1}{2}[/tex]
Substitute x = [tex]\frac{1}{2}[/tex] into either of the 2 equations and evaluate for y
Substituting into (1)
4([tex]\frac{1}{2}[/tex] ) + 3y = 2
2 + 3y = 2 ( subtract 2 from both sides )
3y = 0 ⇒ y = 0
Solution is ( [tex]\frac{1}{2}[/tex], 0 )